Visual Storytelling for Online Learning with the United Nations Sustainable Development Goals - Woodford, E D (Holistic Education Review, 2021)
The United Nations (UN) Sustainable Development Goals (SDG) are calls to action worldwide to make our world better. As part of a larger autoethnographic case study, the author explores strategies to decolonize online education through diversity, equity, inclusion and accessibility. This article demonstrates a chapter of this overall research where a United Nations Fellowship in visual storytelling provides the opportunity to use open pedagogy and create a course where students can tell the stories of their communities across Canada and internationally. Finally, the author demonstrates her own interests in relation to the UN SDG’s and a vision for students to become changemakers in research.